The Analysis of Implementation of Discovery Based Learning to improve Students Higher Order Thinking Skills in Solving r-Dynamic Vertex Coloring Problem Based on Their Reflective Thinking Skill. (March 2019) - Umam, H.; Dafik,; Irvan, M
Abstract: This study aims to analyse the implementation of discovery-based learning in improving students' high-order thinking skills in solving r-dynamic problems based on their reflective thinking ability. The method used in this study is a mixed method, which mix up the qualitative and quantitative methods. The subjects consisted of 18 students in experiment class and 18 students in control class. The post-test result of the experiment class of 11.11% students having low level of high-order thinking ability, and 88.89% having high level of high-order thinking ability with their reflective thinking skill 25% of low level, 68, 75% of medium level, 6, 25% of high level. In the post-test result of the control class, there are 27.78% students having low level of high-order thinking ability and 72.22% students having high level of high-order thinking ability with their reflective thinking skill 53, 85% of low level, 46, 15% of medium level. The data analysis presents the score of independent sample t-test of post-test is sig. 0.05 (p≤0, 05), so it is significant. Therefore, there is a different of their high-order thinking skill ability between the experiment and control classes. The regression equation of both variables expresses 1.497 (Ῡ = −51.067 + 1.497X). The coefficient of determination is 0.575 of 57.5% effect, contribution of the dependent variable (the result of the test post) by the free variable (Discovery based learning) is 57.5% and 42.5% explained by other variables. It implies that we accept the positive hypothesis as tcount > ttable (4.649> 2.119). Thus, there is an impact of the implementation of discovery based learning in improving the students' higher order thinking skills in solving the r-dynamic vertex coloring problem based on their reflective thinking skill.